The Use of Indonesian Language in Education Habitus - Renita Br Saragih (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The purpose of this paper is to reflect on how Indonesian is used in an educational environment. We realize that education is an elementary thing in the life and development of the nation, especially in terms of mentality. Education is regulated under a juridical umbrella, namely Law No. 2 of 2003. In the world of education, ideally, the ability to use language that must be mastered by each individual is the ability to use language properly and correctly, in accordance with applicable language rules. It can be seen how deep the education space is even in this millennial era, which still does not apply these rules, so that the Indonesian language does not look graceful and authoritative. The method of this paper is a literature review using references that are considered compatible in this study. The need for central resources is adjusted to the needs of the study. The results of the study are the tendency to use language that reflects a sense of (1) not being afraid and ashamed of being wrong in pronunciation, (2) not ashamed of losing self-confidence.